Strategi Pembelajaran Kitab Ta'lim Muta'allim Dalam Pembentukan Karakter Santri - Iin Suriya Ningsih; Srinanda Srinanda; Eko Nursalim (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research aims to investigate the impact of Ta'lim Muta'allim book learning strategies on the character formation of Islamic students in boarding schools. Boarding schools play a significant role in character education and the promotion of Islamic values among their students. The Ta'lim Muta'allim book, as a classical text commonly used in boarding schools, is considered to have significant potential in shaping the character of students. The research employed a qualitative case study approach at Al-Ihsan Boarding School, located in Central Java, Indonesia. Data were collected through interviews, observations, and document analysis. The research participants included students and instructors at the boarding school. The findings of the research indicate that the utilization of learning strategies centered around the Ta'lim Muta'allim book significantly contributes to character formation among the students. Students engaged in deep and reflective learning about the contents of the Ta'lim Muta'allim book displayed a substantial improvement in their understanding of Islamic values, ethics, and morality. Furthermore, these learning strategies also played a role in fostering discipline, patience, and perseverance among the students. This research provides valuable insights into the importance of incorporating the Ta'lim Muta'allim book into the boarding school curriculum and employing appropriate learning strategies to achieve character development objectives. These findings can serve as a guide for other boarding schools in their efforts to enhance character education effectiveness in the face of evolving contemporary challenges.